Platinum particle size and support effects in NO(x) mediated carbon oxidation over platinum catalysts - Villani, Kenneth; Vermandel, Walter; Smets, Koen; Liang, Duoduo; van Tendeloo, Gustaaf; Martens, Johan A (Environmental science & technology, 2006)
Platinum metal was dispersed on microporous, mesoporous, and nonporous support materials including the zeolites Na-Y, Ba-Y, Ferrierite, ZSM-22, ETS-10, and AIPO-11, alumina, and titania. The oxidation of carbon black loosely mixed with catalyst powder was monitored gravimetrically in a gas stream containing nitric oxide, oxygen, and water. The carbon oxidation activity of the catalysts was found to be uniquely related to the Pt dispersion and little influenced by support type. The optimum dispersion is around 3-4% corresponding to relatively large Pt particle sizes of 20-40 nm. The carbon oxidation activity reflects the NO oxidation activity of the platinum catalyst, which reaches an optimum in the 20-40 nm Pt particle size range. The lowest carbon oxidation temperatures were achieved with platinum loaded ZSM-22 and AIPO-11 zeolite crystallites bearing platinum of optimum dispersion on their external surfaces.